The relationship and effect of role overload, role ambiguity, work-life balance and career development on work stress among call center executives of business process outsourcing (BPO) in Selangor - Kavitha, Venugopal (2017)
Work stress is a global issue that keep rising among the working adults. The fast growing business pace has created a highly demanding and stressful working environment. Work stress is a phenomena that is extremely threaten for both organization and employees. Consequently, this research is aim to identify the contributing factors of work stress to recognize the effect of highly influencing stressor among call center executives of BPO in Selangor. The four independent variables of this study which consist of role overload, role ambiguity, career development and worklife balance are analyzed to determine the relationship with dependent variable of work stress. Besides, this research had utilized cross-sectional study. The total 152 of respondents are was involved in this study. Data collection was carried out by distributing questionnaires. Additionally, the collected respondents was analyzed by Statistical Package for Social Science (SPSS) version 17.0. The research analysis are consist of descriptive statistics, reliability analysis and inferential analysis to identify the relationship among the independent and dependent variables. The multiple regression analysis shows that role overload (r = .794**, n= 152, p ≤ 0.00) and role ambiguity (r = .251**, n = 152, p≤0.00) has a positive and significant relationship on work stress. Besides that, work-life balance (r = -.183*, n=152, p ≤ 0.05) and career development (r = -.166*, n = 152, p ≤ 0.05) shows a significant and negative relationship on work stress. As overall all, role ambiguity, role overload, career development and work-life balance effect work stress by 65.1% as the R2 value is .651. The study findings shows that role overload are highly significant as the beta value is 784, p ≤0.00 which contributing work stress among call center executives in BPO that located in Selangor. Career development is the second highest beta value. .209, p ≤0.45 that effect work stress. Work-life balance beta value is -.207, p ≤0.45. The beta value of .099, p ≤0.77 shows that role ambiguity has a very low effect on work stress. Moreover, the managerial implication of this study are identified as long working hours and dual processing which are required to be managed in order to control the work stress level among call center executive of BPO in Selangor. Therefore, future research should explore other contributing factors of work stress such as interpersonal relationship and role conflicts. Finally, the research should extend more to other BPO call centers.